2021
DOI: 10.1002/deo2.9
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of sporadic non‐ampullary duodenal epithelial tumors: Can we wait and see?

Abstract: The natural history of sporadic non-ampullary duodenal epithelial tumors (SNADETs) is poorly documented. The aim of this study was to evaluate the history of SNADETs in patients where immediate resection could not be performed. Methods: This is a single-center retrospective study of 86 consecutive cases of SNADETs who did not undergo immediate resection and were followed-up with upper gastrointestinal endoscopy for more than 6 months. Results: During a follow-up period of 36.8 (6.0-613.0) months, macroscopic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, because this was a multicenter retrospective study focusing on follow-up cases, all lesions were not resected. Previous reports on the natural course of SNDA also based their final diagnoses on biopsies in nonresected lesions ( 11 13 ), which can be regarded as a limitation in studies observing the natural course. To mitigate this limitation, we have also shown the cumulative incidence rate of carcinoma confirmed by resection (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because this was a multicenter retrospective study focusing on follow-up cases, all lesions were not resected. Previous reports on the natural course of SNDA also based their final diagnoses on biopsies in nonresected lesions ( 11 13 ), which can be regarded as a limitation in studies observing the natural course. To mitigate this limitation, we have also shown the cumulative incidence rate of carcinoma confirmed by resection (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cassani et al also showed that tumor atypia was exacerbated in some SNDAs ( 12 ). Sakaguchi et al ( 13 ) reported that changes in the macroscopic size or shape of SNDAs indicate a high risk of progression to invasive cancer. In those reports, the progression rate from adenoma to cancer was reported to be 4.3%–5.6% ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, changes in size and macroscopic type have also been regarded as candidate risk factors for invasive cancer. 5 The safety and efficacy of novel new procedures for endoscopic mucosal resection (EMR), such as cold snare polypectomy 6 and underwater EMR [7][8][9] for SNADETs, have been reported. Furthermore, the availability of techniques for endoscopic submucosal dissection (ESD) of large SNADETs have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 4.7% of duodenal adenomas progress to adenocarcinoma, while high‐grade dysplasia and lesions larger than 20 mm are at risk for progression to adenocaricinoma 4 . Recently, changes in size and macroscopic type have also been regarded as candidate risk factors for invasive cancer 5 …”
Section: Introductionmentioning
confidence: 99%